2018
DOI: 10.18632/oncotarget.24809
|View full text |Cite
|
Sign up to set email alerts
|

Liquid biopsy in pancreatic cancer: the beginning of a new era

Abstract: With dismal survival rate pancreatic cancer remains one of the most aggressive and devastating malignancy. Predominantly, due to the absence of a dependable methodology for early identification and limited therapeutic options for advanced disease. However, it takes over 17 years to develop pancreatic cancer from initiation of mutation to metastatic cancer; therefore, if diagnosed early; it may increase overall survival dramatically, thus, providing a window of opportunity for early detection. Recently, genomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 409 publications
(333 reference statements)
0
43
0
Order By: Relevance
“…In fact, liquid biopsy allows traditional limitations of tissue biopsy linked to spatial and temporal heterogeneity to be overcome, with the advantage of being less invasive and easily repeatable. Extensive evidence suggests that high levels of circulating tumor DNA (ctDNA) may predict disease progression in mPC [29][30][31]. To investigate ctDNA in an adjuvant setting could help to select patients with minimal residual disease at risk of post-surgical recurrence, probably even better than the use of circulating tumor cells (CTC) or CA19.9, although nowadays definitive data are not disposable [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, liquid biopsy allows traditional limitations of tissue biopsy linked to spatial and temporal heterogeneity to be overcome, with the advantage of being less invasive and easily repeatable. Extensive evidence suggests that high levels of circulating tumor DNA (ctDNA) may predict disease progression in mPC [29][30][31]. To investigate ctDNA in an adjuvant setting could help to select patients with minimal residual disease at risk of post-surgical recurrence, probably even better than the use of circulating tumor cells (CTC) or CA19.9, although nowadays definitive data are not disposable [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pancreatic cancer, one of the most aggressive tumors, is asymptomatic at an early stage and most diagnosis are made at late stage where there are limited options for treatment [471]. The established biomarker for pancreatic cancer, CA19-9, is not suitable for screening and diagnosis.…”
Section: Towards Unmet Clinical Needsmentioning
confidence: 99%
“…The established biomarker for pancreatic cancer, CA19-9, is not suitable for screening and diagnosis. Moreover, pancreatic cancer has four different subtypes with complex molecular signatures, which are impossible to resolve using current diagnostic procedures [471].…”
Section: Towards Unmet Clinical Needsmentioning
confidence: 99%
“…However, the rate of surgical indication among patients with PC has been reported to be only 20% [3], and the approach for assessing target mutations in the remaining 80% of patients is unclear. Some studies have reported that genetic tests using cytological specimens and liquid biopsy are useful [15,16].…”
Section: Introductionmentioning
confidence: 99%